Concious territorial engagement in the case of Romania - Botos, Attila (Studia Mundi – Economica, 2018)
As for the purpose of my project, I chose the following topic, since the thought of it has always kept my mind occupied, whereas questioning what sort of regional tasks does Romania has to deal with, which are those regional roles, that show within the teaching system, the higher teaching institutions as well as within our culture. The regional development and the spatial planning’s, the urbanism subjects have got my interest most of all, to collect several informations and to do my researches on. With the completion of my theoretical and practical researches my purpose has been to establish – as a result – what are those regional tasks that Romania takes in order to fulfil the citizens’ expectations and requirements.